Baricitinib is potentially effective in the treatment of refractory livedoid vasculopathy - Han, Yuyang; Tu, Ping (Frontiers in Immunology, 2022)
Background Livedoid vasculopathy is a rare, chronic, and recurrent disease with limited effective treatments. Its etiopathogenesis remains incompletely understood. Baricitinib, a selective Janus kinase 1 and 2 inhibitor, has been used to treat rheumatoid arthritis and could reduce the disease severity in patients with livedoid vasculopathy. Methods We retrospectively observed eight patients who received 2 mg/day of baricitinib for the treatment of refractory livedoid vasculopathy. We evaluated their clinical scores before and after treatment to determine its effectiveness and safety. Results Improvement in livedoid vasculopathy was observed with significant regression in the clinical scores after baricitinib treatment. The mean clinical scores were 7.0 ± 1.6 and 1.4 ± 1.2 before and after baricitinib treatment, respectively (P <0.01). Furthermore, six out of the eight patients achieved a clinical score of 0 or 2 after treatment. These scores indicated remission. Clinical findings, including erythema, ulceration, and pain, improved in all the patients. The remission times ranged from 3 to 13 weeks, with a mean remission time of 7.75 ± 3.45 weeks. There were no reports of adverse events in any patient. Conclusions Our study showed that baricitinib treatment was safe and could significantly relieve the signs and symptoms of livedoid vasculopathy. However, randomized controlled studies should be conducted to confirm these results.